Calyx (con)fusion in a hyper-diverse genus: Parallel evolution of unusual flower patterns in Eugenia (Myrtaceae) - Giaretta, Augusto; Vasconcelos, Thais N.C.; Mazine, Fiorella Fernanda; Faria, Jair Eustáquio Quintino; Flores, Rodolfo; Holst, Bruce; Sano, Paulo Takeo; Lucas, Eve (Molecular phylogenetics and evolution, 2019)
[Display omitted] •Eugenia is monophyletic including related genera previously segregated.•Calyx fused species evolved several times in the evolution of Eugenia.•Deep morphological assessment revealed five development patterns of calyx fusion.•Apparently six-petal species are the result of modification of two petaloid sepals.•Eugenia feijoi group can be recognized by the membranisepalous pattern. Eugenia has a pantropical distribution and comprises ca. 1000 species found mostly in the Neotropics. Recent DNA based phylogenies show that unusual flower morphology of ‘eugenioid’ collections, e.g. fused calices that open by tearing, consistently emerged within Eugenia. These results emphasize a demand to revaluate flower morphology in a phylogenetic context within the genus. A reassessment of calyx fusion in Eugenia and traditionally related genera is here focused on clarification of the systematic relevance of this apparently recurrent characteristic. Twenty-four Eugenia species with some level of calyx fusion in the bud were newly used (one nuclear and four plastid markers) in conjunction with a representative sample of previously sequenced species to recover a time-calibrated Eugenia phylogeny of 86 accessions. Development of the fused calyx was analysed using scanning electron microscopy, differing patterns were re-coded and subsequently phylogenetic character reconstruction was performed. Eugenia was recovered as monophyletic including the traditionally segregated genera Calycorectes and Catinga. Ancestral character reconstruction uncovered free calyx lobes as the ancestral condition. Five development patterns leading to calyx fusion are reported in Eugenia including species with apparently six petals, which contrast with the standard tetramerous flowers. This condition is interpreted as the petaloid pattern, where two external fused calyx lobes cover the bud while two internal calyx lobes are free and petaloid. The fused calyx condition is homoplastic and evolved independently, several times in Eugenia, as did the different development patterns. Data presented here show that systematic incongruence resulting from multiple, independent origins of the fused calyx in Eugenia is further aggravated by an inability to distinguish parallelism and convergence within the recovered patterns.